"Green" Synthesis of Noble Metal Nanoparticles and CdS Semiconductor Nanocrystals Using Biological Materials - Blume, Ya.B.; Pirko, Ya.V.; Burlaka, O.M.; Borova, M.M.; Danylenko, I.A.; Smertenko, P.S.; Yemets, A.I. (Science and Innovation, 2024)
The basic principles of synthesis of metal nanoparticles and semiconductor nanocrystals as well as the prospects for their application have been discussed. The relevance of living systems and their components for the development of «green» technology for synthesizing nano-objects with unique properties and a wide range of applications has been analyzed. The biotechnological synthesis of silver, gold, and silver-gold bimetallic nanoparticles using plant extracts of Magnolia denudata, M. stellata, Camellia sinensis var. sinensis, C. sinensis var. assamica, Orthosiphon stamineus, and Hypericum perforatum has been described. The results of synthesis of cadmium sulfide fluorescent semiconductor nanocrystals using Escherichia coli bacteria, Pleurotus ostreatus basidiomycete and Linaria maroccana plant have been reported. Morphological and optical characteristics of the synthesized nanoparticles have been described.